2014
DOI: 10.1021/cg500722n
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of In2Se3/Si(111) Heteroepitaxy To Enable Bi2Se3/In2Se3 Bilayer Growth

Abstract: Systematic optimization of molecular beam epitaxy growth parameters enabled high quality heteroepitaxy of In 2 Se 3 on Si(111) surfaces. Surfaces of the best epilayers were characterized by atomically flat terraces that extended laterally for several hundred nanometers. These terraces were separated by single quintuple layer high steps. These In 2 Se 3 films were suitable for subsequent high quality epitaxy of Bi 2 Se 3 . The quality of the In 2 Se 3 /Bi 2 Se 3 interface was confirmed using atomic resolution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Thus, theoretically, using In 2 Se 3 as a buffer layer could enhance the crystal quality of Bi 2 Se 3 films. Systematic optimization of MBE growth parameters of In 2 Se 3 on Si(111) substrate was reported by Rathi et al [43]. The authors concluded that the In 2 Se 3 layers that are most suitable for Bi 2 Se 3 growth resulted from a three-step growth sequence: Se passivation of the Si substrate at 100 • C, In 2 Se 3 codeposition with a temperature ramp from 100 • C to 400 • C, followed by Se anneal at 400 • C. They also successfully grew Bi 2 Se 3 on top of In 2 Se 3 with a sharp interface.…”
Section: Aging Effectsmentioning
confidence: 99%
“…Thus, theoretically, using In 2 Se 3 as a buffer layer could enhance the crystal quality of Bi 2 Se 3 films. Systematic optimization of MBE growth parameters of In 2 Se 3 on Si(111) substrate was reported by Rathi et al [43]. The authors concluded that the In 2 Se 3 layers that are most suitable for Bi 2 Se 3 growth resulted from a three-step growth sequence: Se passivation of the Si substrate at 100 • C, In 2 Se 3 codeposition with a temperature ramp from 100 • C to 400 • C, followed by Se anneal at 400 • C. They also successfully grew Bi 2 Se 3 on top of In 2 Se 3 with a sharp interface.…”
Section: Aging Effectsmentioning
confidence: 99%